(untitled) (Transport systems and technologies, 2023)
The article analyses the known experimental results of the assessment of the level of damage of structural materials of various grades under the conditions of long-term, cyclic, static loading, and lubricated friction. The structural changes that occur in the materials during loading have been shown with correlate to the changes in the statistical scattering characteristics of the hardness measurement results. This enables prediction of the kinetics of damage accumulation in materials during operation and, therefore, prediction of their service life. This approach is relevant for the development of methods for the assessment of the current condition and residual life of structures in the railway and other transport industries. It is proposed to use this methodology to evaluate the level of damage to the microstructure of materials in the contact zone and its impact on the tribological characteristics of metal friction pairs. A new method is proposed for the performance assessment of lubricating compositions based on industrial lubricants that contain nano-additives of different chemical compositions for higher wear resistance of heavy-loaded steel friction pairs. The method is based on the joint analysis of the experimental data on the wear kinetics, variation of the relative hardness, and level of damage in the surface layers of the metal friction pairs. The structural damage of the materials in the contact zone is determined by employing the statistical parameters of scattering of the hardness values. The methodology has been approved for steel friction pairs where lubricants based on industrial oil and on nano-additives of copper, magnesium alloy, graphite, and two grades of medium-carbon steels, are used.